Feeding preferences of Oxpeckers in Kruger National Park, South Africa. - Ndlovu, M.; Combrink, L. (AOSIS OpenJournals Publishing AOSIS (Pty) Ltd, 2015)
Oxpeckers reduce tick loads on ungulate hosts, but they are also known to feed on and exacerbate wounds. An understanding of the feeding behaviours and host preferences of these birds is important since they serve as agents of tick control on both domestic and wild ungulates. We conducted an observational study at two sites within the Kruger National Park in South Africa, exploring the feeding preferences of both Red-billed and Yellow-billed Oxpeckers. Oxpeckers’ host preferences, body-location preferences on different hosts, prevalence of feeding and non-feeding behaviours, and frequency of tolerance versus rejection in different hosts were determined. It was found that Yellow-billed Oxpeckers had a smaller range of hosts – typically larger-sized ungulates – and that Red-billed Oxpeckers diversify to smallersized ungulate hosts when in competition with Yellow-billed Oxpeckers. Body-location preferences were generally consistent across sites and across host species. Tick feeding and other host-feeding behaviours (around the eyes, nose, mouth and ears, and anogenital areas) were fairly common. Only six incidents of wound feeding, from a total of 855 observations, were recorded. Tolerance by an ungulate host species was not related to Oxpeckers’ host preferences, suggesting that other factors such as ungulate body size, tick species and tick stages on the host animal may play a significant role in the feeding preferences of Oxpeckers. Conservation implications: It is important to study Oxpeckers’ behavioural feeding preferences so as to better understand their ecology and present distribution, and to determine where they can be reintroduced in future. Reintroduction not only helps with the proliferation of Oxpeckers, but also benefits ungulate hosts through ectoparasite removal and the subsequent control of tick-borne diseases.
Keywords: bird; ectoparasite; feeding behavior; host preference; reintroduction; tick; ungulate; Kruger National Park; South Africa; Animalia; Aves; Buphagus erythrorhynchus; Ixodida; Ungulata